Determination of the Iodine Content of Some Commonly Consumed Foods in Zaria Metropolis, Nigeria, Using PCNAA and Sandell-Kolthoff Reaction. (20th July 2014) - Muhammad, T.; Uzairu, A.; Sallau, M. S.; Oladipo, M. O. A.
Abstract : The Nigerian Research Reactor-1 was employed in the analysis of iodine in local food samples at an operating flux of5.0 × 10 11 ncm −2 s −1 . Preconcentration neutron activation analysis (PCNAA) was compared against the most common spectroscopic (Sandell-Kolthoff reaction) technique, giving a concentration range of 0.295 to 2.960 mg/Kg and 0.264 to 2.725 mg/Kg, respectively, with an average percentage deviation of 11.34% and a positive correlation between the methods at 0.89. PCNAA and Sandell-Kolthoff spectroscopy of NIST 1548a reported values of0.759 ± 0.06 mg/Kg and0.751 ± 0.05 with Student's t -test score of 1 and 0.95 and percentage standard deviation of 0 and 1.12%, respectively.